Anionic Intercalation: Transparent and Flexible Mn1−x−y(CexLay)O2−δ Ultrathin‐Film Device for Highly‐Stable Pseudocapacitance Application (Adv. Funct. Mater. 30/2021). (22nd July 2021) - Maroufi, Samane; Khayyam Nekouei, Rasoul; S. Mofarah, Sajjad; O'Mullane, Anthony P.; Yao, Yin; Lim, Sean; Cazorla, Claudio; Sahajwalla, Veena
Abstract : In article number 2100880, Samane Maroufi and co‐workers report the synthesis of defect‐rich Mn1− x − y (Ce x La y )O2−δ ultrathin films with controllable thicknesses, transmittance, and outstanding areal capacitance. The performance originates from the intercalation/de‐intercalation of anionic O 2− charges and intervalence charge transfer among cations with multioxidation states. This method has the potential for large‐scale and cost‐effective fabrication of stable and flexible pseudocapacitors.